GENE-05. ATRX IN-FRAME FUSION NEUROBLASTOMA IS SENSITIVE TO EZH2 INHIBITION VIA MODULATION OF NEURONAL GENE SIGNATURES. (23rd April 2019) - Qadeer, Zulekha; Valle-Garcia, David; Hasson, Dan; Soriano, Aroa; Ma, Anqi; Griffiths, Lyra; Zeineldin, Maged; Sun, Zhen; Jubierre, Luz; Filipescu, Dan; Chowdhury, Asif; Deevy, Orla; et al.
Abstract: Mutations and structural alterations of the SWI/SNF-like chromatin remodeler ATRX (Alpha Thalassemia/Mental Retardation, X-linked) have been reported at high frequency in a number of adult and pediatric tumors. However, the consequences of ATRX mutations in cancer and their impact on the epigenome remain ill defined. Particularly intriguing are the large N-terminal deletions of ATRX in neuroblastoma that generate in-frame fusion (IFF) proteins devoid of key chromatin interaction domains, while retaining the SWI/SNF-like helicase domain. We hereby demonstrate that ATRX IFF proteins have distinct genomic distribution compared to wild type (WT) ATRX and are absent from H3K9me3-enriched chromatin, yet bound to active promoters. We find REST (RE-1 Silencing Transcription Factor) as one such ATRX IFF target that is activated and promotes silencing of neuronal differentiation genes. Notably, we uncover that ATRX IFF cells display exquisite sensitivity to EZH2 inhibitors (EZH2i) in vitro and in vivo, due in part to derepression of neurogenesis genes, including a subset of REST targets. Examination of the epigenomic landscape of neuroblastoma tumor specimens harboring ATRX IFFs reveals that H3K27me3 occupies a subset of neurogenesis genes that are transcriptionally silenced and sensitive to EZH2i in our cell-based assays. In summary, this study demonstrates that ATRX structural alterations are not loss-of-function as predicted, and supports EZH2i as a key therapeutic strategy for ATRX IFF neuroblastoma.